CNC Machines for Rehabilitation: Ankle and Shoulder - Andrés Blanco Ortega; Andrea Magadán Salazar; César. H. Guzmán Valdivia; Fabio Abel Gómez Becerra; Manuel J. Palacios Gallegos; Miguel A. García Velarde; José Alfonso Santana Camilo (Machines, 2022)
Continuous passive motion (CPM) machines are used in the rehabilitation of members that have been injured to recover their range of motion and prevent stiffness. Nowadays, some CPM machines for the knee, ankle, arm, and elbow are available commercially. In this paper, ankle and shoulder rehabilitation robots, based on an X-Y table, are presented. The novelty of these rehabilitation robots is that they have a computerized numerical control system, resulting in low-cost machines. Some G-codes for basic and combined movement routines for ankle and shoulder rehabilitation are presented. In addition, the use of a robust generalized PI controller is also proposed to guarantee safe rehabilitation movements and compensate for passive stiffness in the ankle joint of stroke survivors. Some numerical simulations are included to illustrate the dynamic performance of the robust Generalized Proportional Integral (GPI) controller using the virtual prototype.